Manipulation of Sulfur Vacancies and Dislocations in Mn0.3Cd0.7S Nanorods with Modification of Co2P toward Photocatalytic H2 Evolution. Issue 10 (29th July 2022) - Han, Yanling; Feng, Xiao; Gan, Bin; He, Jiari; Feng, Jianyong; Zhao, Minyue; Li, Zhaosheng; Zou, Zhigang
Abstract : Defect engineering and cocatalyst loading are effective methods to modify semiconductors to improve their catalytic activity and stability. Herein, sulfur vacancies and dislocations in Mn0.3 Cd0.7 S nanorods are manipulated by regulating the amount of the sulfur source. After the introduction of Co2 P, the maximum H2 production rate for Co2 P/Mn0.3 Cd0.7 S can reach up to 245.3 μmol h −1, ≈2, 700 times higher than that of Mn0.3 Cd0.7 S at the optimal contents of sulfur vacancies and dislocations. The sulfur vacancies serve as the trap sites of electrons and the dislocations might create new transfer channels for carriers, inducing the improvement of catalytic activity and stability. Abstract : The sulfur vacancies and dislocations in Mn0.3 Cd0.7 S nanorods are manipulated by changing the amount of sulfur source added. After the introduction of Co2 P cocatalysts on the surface of Mn0.3 Cd0.7 S nanorods, the optimal H2 evolution rate can reach up to 245.3 μmol h −1, exceeding that of pure Mn0.3 Cd0.7 S by ≈2, 700 times.